Measurement of wet antenna effect on microwave propagation at 23, 26 and 38 GHz - Islam, M. R.; Abdul Rahman, Tharek (Institute of Electrical and Electronics Engineers (IEEE), 2000)

(untitled)
Losses due to water being in or on the surface of the radomes or the parabolic reflector and on the feed window of antennas are occurred during rain. An experiment has been done to measure the losses on the antennas due to rain by spraying water. In order to separate this loss from the propagation loss, an analytical approach has been proposed. A physical model for wet antenna loss has been developed based on measured one year rain attenuation and rainfall statistics in Malaysian tropical climate